Zanesljivost in veljavnost v slovenščino prevedenega vprašalnika o težavah zaradi fibromialgije - Sonc, Marjana (Rehabilitacija (Ljubljana), 2010)
Background: The fibromyalgia syndrome is a pathogenetically and ethiologically unexplained chronic pain syndrome. Reliability and validity of self-administered questionnaires are the basic criteria for measuring disability of patients with fibromyalgia for clinical decision making. The aim of this study was to determine validity and reliability of the Slovenian translation of the Fibromyalgia Impact Questionnaire (FIQ). Methods: The questionnaire was translated into Slovenian and sent to 83 persons with fibromyalgia symptoms. The questionnaire was sent twice (with one-month interval) by surface mail. Reliability was examined in terms of internal consistency and stability over time. Predictive and convergent validity were also evaluated. Results: 36 female patients with an average age of 45 years responded. Cronbach Alpha for the translated FIQ was 0.71, which indicates sufficient internal consistency. The average score did not differ significantly between the two time-points (1st completion: M=59.4, SD=11.1; 2nd completion: M=58.3, SD=12.4; p=0.469). Intraclass corellation was 0.69, which indicates sufficient stability over time. Predictive validity was demonstrated by FIQ score being moderately positively corellated with duration of absence from work due to fibromyalgia (r=0.37; p=0.050) and highly positively corellated with self-assessment of symptoms' influence on the ability of performing different tasks (r=0.69; p<0.001). Physical and mental health components of the SF-36 were - like most SF-36 subscales - statistically significantly negatively corellated with FIQ score. Coclusions: The Slovenian translation of the FIQ is sufficiently reliable for use in clinical practice. The results also speak in favour of predictive and convergent validity, but other metric characteristics should be examined further.
Keywords: bolečina; diagnostika; fibromialgija; vprašalniki